Challangeging in Writing Skill: students’ and Lecturer’s Perception - Salva Dilla Oktavia; Ahmad Syafiq; Dyah Sih Pratiwi (Departement of Mathematics Education, 2024)
The aims of this research is to know the students’ and lecturer’s problems in Writing skill. This research is a qualitative research. This research used questionnaires and interview as instrument. The sample of this research is students in first semester in one of University in Lampung. The questionnaires and interview were recorded and transcribed. The researcher analyzed the result of questionnaires and interview and explain the result in descriptive way. Based on the data, there were three factors that making students’ problems in writing skill namely; lack of knowledge (27%), lack of vocabularies (32%) and lack of grammar (41%). In the other hand there were three factors in lecturer’s perception such as less of facilities (29%), less of respond of students (33%), and less of teaching style (38%). These factors were caused the result of writing skill in the end of subject.